Improved properties of carbon fiber paper as electrode for fuel cell by coating pyrocarbon via CVD method - 谢志勇 金谷英 张敏 苏哲安 张明瑜 陈建勋 黄启忠 (Transactions of Nonferrous Metals Society of China, 2010)
The fabrication of a pyrocarbon coated carbon paper and its application to the gas diffusion lay （GDL） of proton exchange membrane （PEM） fuel cell were described. This carbon paper was fabricated by using conventional carbon paper as the precursor, and coating it with pyrocarbon by pyrolyzing propylene via the chemical vapor deposition （CVD） method. For comparison, conventional carbon paper composites were also prepared by using PAN-based carbon fiber felt as the precursor followed by impregnation with resin, molding and heat-treatment. SEM characterization indicates that pyrocarbon is uniformly deposited on the surface of the fiber in the pyrocarbon coated carbon paper and made the fibers of carbon felt bind more tightly. In contrast, there are cracks in matrix and debonding of fibers due to carbonization shrinkage in the conventional carbon paper. Property measurements show that the former has much better conductivity and gas permeability than the latter. In addition, current density-voltage performance tests also reveal that the pyrocarbon coating can improve the properties of carbon paper used for electrode materials of fuel cell.